Determinants of online cash waqf acceptance - Farah Yasmin Azman; Nurul Shafika Zulkifli; Sha Fatin Najia Jeffry; Wan Nur Faqihah Wan Zuraizihan (2022)
The digitalization has been implied in all sector in order to make the activity and transaction better and smoother. Thus, it also been used thoroughly especially during Pandemic Covid 19 that limit people’s movement which is Movement Control Order (MCO). The digitalization is not only focusing on e-commerce, e-banking and e-hailing. Yet, the waqf industry also implement various strategy to gain fund by make use of advance technology and digitalization. Therefore, this study aims to investigate the determinant of online cash waqf acceptance. This study uses quantitative research and researcher collect data from secondary source from other authors to examine the relationship between four independent variables and online cash waqf acceptance. This study also targeted Muslim donors in Pengkalan Chepa as respondent then use simple random sampling in probability technique. The data were collected via online platform which is Google Form in order to approach and reach the respondents of Muslim donor in Pengkalan Chepa that use digitalization in doing waqf transaction. In this case, there were four main determinants that impact the acceptance level of online cash waqf which are perceived of usefulness, perceived of ease of use, perceived of religiosity and amount of information. The total number of respondents were 278 involved in this study and tested using Statistical Package for the Social Science (SPSS). The questionnaire was construct by using 5 point of Likert scale that ranges from 1 (Strongly disagree) to 5 (Absolutely agree) and has three sections which are section A (demography), section B (determinants of online cash waqf acceptance) and section C (online cash waqf acceptance). The finding of this study is strong positive relationship between all four independents variable and the dependent variable.